Isolation of a high-ammonium-tolerant Monoraphidium sp. and evaluation of its potential for biodiesel production. (December 2021) - Lin, Yimeng; Song, Gang; Ling, Hongzhi; Ge, Jingping; Ping, Wenxiang
Graphical abstract: Highlights: Microalgal strain HDMA-01 was isolated and identified as a novel Monoraphidium sp. HDMA-01 grows robustly at high ammonium concentrations. The high lipid and ideal fatty acid profile make HDMA-01 a good biodiesel feedstock. The ammonium tolerance of HDMA-01 implied its application potential in biotechnology. Abstract: The economic challenges of microalgae biodiesel production, including the energy burden and water shortage, can be addressed simultaneously by using wastewater as a nitrogen source. However, as a major form of nitrogen, ammonium is toxic to most microalgae strains, which limits the use of ammonium-containing wastewater. High-ammonium-tolerant algal strains remain to be explored. In this study, a microalgal strain named HDMA-01, which was isolated from Lake Dongfeng in China, was selected using a high ammonium medium. Phylogenetic analysis suggested that HDMA-01 belongs to the genus Monoraphidium (Selenastraceae, Sphaeropleales), and both 18S ribosomal DNA and ITS sequences of HDMA-01 appeared to be new molecular records of the Monoraphidium species. HDMA-01 can multiply vigorously using acetic acid and ammonium in TAP medium, reaching a density of 2 ×10 7 mL −1 within 7 days. HDMA-01 showed strong tolerance for ammonium. At a high ammonium concentration of 14 mM, HDMA-01 achieved maximum biomass and lipid productivity of 78.9 mg L −1 day −1 and 13.8 mg L −1 day −1, which is the highest among other Monoraphidium strains under similar cultivation conditions. Together with its ideal fatty acid profile, HDMA-01 has great potential for development as a promising strain used in biodiesel feedstock and high-ammonium tolerance biotechnology.